The Second Skin of Seagrass Leaves: A Comparison of Microalgae Epiphytic Communities Between Two Different Species Across Two Seagrass Meadows in Lesser Sunda Islands - Putu Satya Pratama Atmaja,; Dietriech G. Bengen,; Hawis H. Madduppa, (Tropical Life Sciences Research, 2021)
Epiphytes as the important features in the seagrass ecosystems have been studied widely, and their functions as a primary producer, influence rates of herbivory grazer, and prevent seagrass leaf from desiccation is well known. However, patterns and distribution among seagrasses especially in Indonesia, which was known as hotspot marine biodiversity is not well understood. Therefore, this study aimed to examined epiphytic assemblages on two seagrass species with different morphological and longevity, Enhalus acoroides and Cymodocea rotundata, in two different meadows (conservation area and non-conservation area) in Lesser Sunda Islands (Bali and Lombok). A total of 22 taxa of microalgae epiphytes species were identified from eight sites and 2 different species of seagrass. The highest number of collected species between class was from Bacillariophyceae (18), followed by Cyanophyceae (3) and Fragilariophyceae (1). Analysis of similarity (ANOSIM) revealed a significant difference of microalgae epiphytes assemblages between sites and seagrasses. Epiphytes assemblages in conservation area were more abundant than non-conservation area, both in Bali and Lombok. On seagrass comparison, Enhalus acoroides showed higher abundance of epiphytes assemblages than those on Cymodocea rotundata. Based on principal component analysis (PCA), this study highlights the microalgae epiphytic communities strongly influenced by seawater temperature, phosphate’s concentration, and pH in sediment. This study also demonstrated that the assemblages of microalgae epiphytic communities affected by differences of seagrass morphological and longevity.